2021
DOI: 10.1051/shsconf/20219002005
|View full text |Cite
|
Sign up to set email alerts
|

Academic Entrepreneurship Education: Does Gender Matter?

Abstract: Academic entrepreneurship education aims to train and raise awareness amongst students about entrepreneurial activity, thereby increasing the number of academic start-ups and spin-offs. However, as yet, there are very few findings on the gender-specific differences amongst potential entrepreneurs. Building on the current state of research, gender-specific differences in the form of various different components of entrepreneurial competence are examined. This study focuses in particular on (1) entrepreneurial k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Our results contradict, to some extent, Adachi and Hisada’s ( 2016 ) study, which posits that, in general, women have less inclination towards intrapreneurship than men. Relatedly, Justus ( 2021 ) concluded that female students scored less than their male counterparts in four out of five components of entrepreneurial competence included in her study (i.e., entrepreneurial knowledge, domain-specific interest in entrepreneurship, interest in leadership roles, and entrepreneurial intention). However, they are more likely than men to become intrapreneurs when they work for a small firm.…”
Section: Discussionmentioning
confidence: 95%
“…Our results contradict, to some extent, Adachi and Hisada’s ( 2016 ) study, which posits that, in general, women have less inclination towards intrapreneurship than men. Relatedly, Justus ( 2021 ) concluded that female students scored less than their male counterparts in four out of five components of entrepreneurial competence included in her study (i.e., entrepreneurial knowledge, domain-specific interest in entrepreneurship, interest in leadership roles, and entrepreneurial intention). However, they are more likely than men to become intrapreneurs when they work for a small firm.…”
Section: Discussionmentioning
confidence: 95%
“…However, research on entrepreneurship education ecosystem (FEE) specially for female college students is limited, which explains the potentially unrepresented youth and female entrepreneurs. The current entrepreneurship education should be adapted for female students, generating a new format of female-targeted measures in multiple dimensions (Justus, 2021). Consequently, this study aims to propose a female entrepreneurship education ecosystem (FEEE) to empower female students with customized FEE by introducing a gender perspective into the current entrepreneurship education ecosystem.…”
Section: An Innovative Feee In China 1177mentioning
confidence: 99%
“…Dalam era globalisasi, di mana batas-batas antarnegara semakin terbuka dan informasi dapat dengan mudah tersebar, persaingan untuk mendapatkan pekerjaan menjadi lebih ketat [14]. Faktor-faktor seperti pertumbuhan populasi, perkembangan teknologi, dan perubahan dalam struktur ekonomi juga berkontribusi terhadap tantangan pengangguran [15]. Penting untuk mencari solusi yang holistik dan berkelanjutan untuk mengatasi masalah pengangguran ini, termasuk dengan meningkatkan kualifikasi dan keterampilan tenaga kerja, mendorong inovasi dan kewirausahaan, serta mengembangkan kebijakan ekonomi yang mendukung penciptaan lapangan kerja [16].…”
Section: Pendahuluanunclassified